1996
DOI: 10.1007/bf00023865
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of stylar ribonuclease zymograms with incompatibility alleles in sweet cherry

Abstract: Protein stylar extracts of 16 cultivars of sweet cherry (Prunus avium), from the 10 different incompatibility groups to which incompatibility alleles have been assigned, were separated on acrylamide gels using isoelectric focusing (IEF) and were stained for ribonuclease activity. When two cultivars from the same incompatibility group were analyzed they gave identical zymograms and the cultivars of the 10 different incompatibility groups gave in all eight distinct zymograms. The ribonuclease polymorphism could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
4
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 8 publications
4
153
4
6
Order By: Relevance
“…From a cross-pollination study, Matthews and Dow (1969) assigned cultivars to 13 incompatibility groups and a Group O, which includes cultivars that are SI but able to pollinate cultivars in all other groups (universal pollen donor). Bošković and Tobutt (1996) reported that RNase zymograms were associated with S-alleles. On the basis of zymograms of stylar proteins, S-alleles of some cultivars were assigned and new S-alleles were detected.…”
Section: Subgenus Cerasus (Cherries) 1) Identification Of S-rnase Allmentioning
confidence: 99%
“…From a cross-pollination study, Matthews and Dow (1969) assigned cultivars to 13 incompatibility groups and a Group O, which includes cultivars that are SI but able to pollinate cultivars in all other groups (universal pollen donor). Bošković and Tobutt (1996) reported that RNase zymograms were associated with S-alleles. On the basis of zymograms of stylar proteins, S-alleles of some cultivars were assigned and new S-alleles were detected.…”
Section: Subgenus Cerasus (Cherries) 1) Identification Of S-rnase Allmentioning
confidence: 99%
“…A maioria das cultivares de P. salicina são autoinférteis, devido ao sistema de autoincompatibilidade gametofítica, determinado pela presença de um loco multialélico, contendo os denominados alelos-S, que codificam para enzimas que interrompem a formação do tubo polínico no processo de polinização (KAUFMANN et al, 1992;NEWBIGIN et al, 1993;BOSKOVIC;TOBUTT, 1996;DE NETTANCOURT, 1997, 2000SAPIR et al, 2004). Como resultado, existe a necessidade do uso de outras cultivares de ameixeira, que servirão como polinizadoras das cultivares produtoras, possibilitando a fecundação, frutificação e boa produção de frutos.…”
Section: Introductionunclassified
“…Studies with RAPD and SCAR markers revealed that only the marker OPI07 750 , closely linked to the S 2 allele, was useful for marker-assisted selection of individuals with the S 2 allele [27]. In apple and almond, with gametophytic incompatibility, S-allele genotyping can be performed using a protein-based method that looks at differences in S-RNase migration through a protein gel [28] or by PCR amplification of genomic DNA with "allele-specific" primers [29,30]. Van Nerum et al [31] reexamined the self-incompatibility genotypes of apple cultivars containing putative "new" S-alleles using S-allelespecific PCR and sequence analysis.…”
Section: Discussionmentioning
confidence: 99%